2020
DOI: 10.2217/epi-2020-0022
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Anxiety and Depression in Pregnancy and DNA Methylation of the NR3C1 Glucocorticoid Receptor Gene

Abstract: Aim: To quantify associations of anxiety and depression during pregnancy with differential cord blood DNA methylation of the glucorticoid receptor ( NR3C1). Materials & methods: Pregnancy anxiety, trait anxiety and depressive symptoms were collected using the Pregnancy Related Anxiety Scale, State-Trait Anxiety Index and Edinburgh Postnatal Depression Scale, respectively. NR3C1 methylation was determined at four methylation sites. Results: DNA methylation of CpG 1 in the NR3C1 CpG island shore was higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Maternal community deprivation during the second or third trimester of pregnancy was found to be significantly associated with greater infant DNA methylation in eight CpG sites of the SLC6A4 gene, but not of the NR3C1 gene [ 46 ]. Dereix et al [ 47 ] recently reported higher NR3C1 methylation in infants of mothers with high levels of prenatal anxiety, but not depression, although gestational timing of exposure was not specified. Similarly, in a cohort of 83 pregnant women, prenatal maternal anxiety was found to be significantly linked with infant NR3C1 methylation in specific CpG sites located into exon 1F [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal community deprivation during the second or third trimester of pregnancy was found to be significantly associated with greater infant DNA methylation in eight CpG sites of the SLC6A4 gene, but not of the NR3C1 gene [ 46 ]. Dereix et al [ 47 ] recently reported higher NR3C1 methylation in infants of mothers with high levels of prenatal anxiety, but not depression, although gestational timing of exposure was not specified. Similarly, in a cohort of 83 pregnant women, prenatal maternal anxiety was found to be significantly linked with infant NR3C1 methylation in specific CpG sites located into exon 1F [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal community deprivation during the second or third trimester of pregnancy was found to be signi cantly associated with greater infant DNA methylation in 8 CpG sites of the SLC6A4 gene, but not of the NR3C1 gene [43]. Dereix and colleagues [44] recently reported higher NR3C1 methylation in infants of mothers with high levels of prenatal anxiety, but not depression, although gestational timing of exposure was not speci ed. Similarly, in a cohort of 83 pregnant women, prenatal maternal anxiety was found to be signi cantly linked with infant NR3C1 methylation in speci c CpG sites located into exon 1F [45].…”
Section: Discussionmentioning
confidence: 99%
“…There may be a dose–response effect, with higher levels of methylation in pregnant women with more severe depressive symptoms. However, a recent study conducted among 163 mother–infant dyads in the United States reported that methylation of NR3C1 gene was not associated with depressive symptoms ( 49 ). The sample used in the US study was cord blood, whereas venous blood from the mother was used in our study.…”
Section: Discussionmentioning
confidence: 99%